Athanasius - Leithart, Peter J. (Grand Rapids, Mich. : Baker Academic, 2011)
This volume offers consideration of the work of famous fourth-century church father Athanasius, giving specific attention to his use of Scripture, his deployment of metaphysical categories, and the intersection between the two. --from publisher description
Introduction : scripture and metaphysics (in the Augustinian mode) -- Evangelizing metaphysics -- Types, terms, and paradigms -- The one God -- Beginnings : word and world -- Middle : God for us -- End : God made man, man made God -- Epilogue (again in the Augustinian mode).
Includes bibliographical references (p. 195-199) and index.
Keywords: Athanasius, -- Saint, Patriarch of Alexandria, -- d. 373.